2008
DOI: 10.1088/0954-3899/36/1/015108
|View full text |Cite
|
Sign up to set email alerts
|

Search for the α +6He decay of10Be via the16O(18O,10Be*)24Mg reaction

Abstract: A search for the α + 6 He decay of 10 Be has been performed using the Li 2 O( 18 O,α 6 He) reaction at 80 and 100 MeV. An array of two Si-Si-CsI telescopes was used for the coincident detection of the breakup fragments. No evidence for the 16 O( 18 O,α 6 He) 24 Mg reaction was obtained, the cross-section being determined as σ < 1.9 μb and <3.9 μb at 80 and 100 MeV, respectively. The α + 15 N decay of 19 F was observed via the 7 Li( 18 O,α 15 N) 6 He reaction. For the 19 F excitation energy and centre-of-mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For cluster states having an α cluster around a core nucleus, well-known examples are 16 O+α states in 20 Ne and 12 C+α states in 16 O [6]. Recent experimental and theoretical studies have revealed many cluster resonances in highly excited states near the α-decay threshold also in unstable nuclei, for instance, A−4 He+α states in Be isotopes [1,4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], 10 Be+α states in 14 C [27][28][29][30]54], 14 C+α states in 18 O and their mirror states [31][32][33][34][35][36][37][38][39][40], 18 O+α states in 22 Ne [38]…”
Section: Introductionmentioning
confidence: 99%
“…For cluster states having an α cluster around a core nucleus, well-known examples are 16 O+α states in 20 Ne and 12 C+α states in 16 O [6]. Recent experimental and theoretical studies have revealed many cluster resonances in highly excited states near the α-decay threshold also in unstable nuclei, for instance, A−4 He+α states in Be isotopes [1,4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], 10 Be+α states in 14 C [27][28][29][30]54], 14 C+α states in 18 O and their mirror states [31][32][33][34][35][36][37][38][39][40], 18 O+α states in 22 Ne [38]…”
Section: Introductionmentioning
confidence: 99%